THE EU AND INDIA IN THE POLARIZED WORLD - Aleksandar Petrović; Aleksandra Stevanović (Przegląd Geopolityczny)
The paper explores basic political relations between the European Union and India which are at theoretical level almost “terra nullius”. The paper starts from the present epochal situation and enters the realm of EU–India geopolitics from the perspective of Gandhian moral practice on one side, and challenges presented by the impact of Coronavirus politics on the other. Our question is – on which platform is strategic negotiating between the EU and India possible? Despite their Lisbon summit in 2000 as well as virtual summit in 2020, it is obvious that until today the EU and India could not find a common denominator. Our idea is that the missing link of a better understanding partly lays in the new perspective that may be unexpectedly found from the Balkans’ point of view. Only unprecedented cognizance today may set up the roadmap for the times to come.